Rebuilding the Northeast Arctic Cod Fisheries - Economic and Social Issues - Armstrong, Claire W.; Eide, Arne; Flaaten, Ola; Heen, Knut; Kaspersen, Inga Wigdahl (Gyldendal Akademisk, 2014)
The Northeast Arctic cod (NEA cod) fisheries in Norway are now one of the richest cod fisheries in the world. In the past the fishery has experienced several stock declines and low economic returns. In this paper we review management approaches applied over 20 years to address one of the most severe crises in the fishery. Emphasis is on management strategies and the measures carried out to ensure successful rebuilding of the fishery, both biologically and economically. Though the rebuilding of the Northeast Arctic cod fisheries has in many ways been a success, a multitude of issues connected to social and economic consequences still remain. The lessons learned from this study relate to management, legitimacy, and economic issues, and may be relevant to other struggling fisheries.